A Systematic Review and Meta-Analysis of Randomized Controlled Trials on the Effects of Oats and Oat Processing on Postprandial Blood Glucose and Insulin Responses. Issue 2 (9th December 2020) - Musa-Veloso, Kathy; Noori, Daniel; Venditti, Carolina; Poon, Theresa; Johnson, Jodee; Harkness, Laura S; O'Shea, Marianne; Chu, YiFang
ABSTRACT: Background: Oats are a whole grain cereal with potentially favorable effects on the postprandial glycemic response; however, the effects of oat processing on these glycemic benefits are not well understood. Objectives: The study objective was to determine the effects of differently processed oats on the postprandial blood glucose and insulin responses relative to refined grains. Methods: Eleven electronic databases were systematically searched to identify studies published up to and including May 2019. Randomized controlled trials comparing the postprandial blood glucose and insulin responses to oats compared with any refined grain were included, so long as the available carbohydrate content of the test meals was similar. Pooled effect sizes were computed using the difference in incremental area under the curves for blood glucose and insulin following the consumption of oats compared with the refined grain control. Results: Ten publications were included, with intact oat kernels studied in 3 comparisons, thick oat flakes (>0.6 mm) in 7 comparisons, and thin/quick/instant oat flakes (≤0.6 mm) in 6 comparisons. Compared with the consumption of the refined grain control, the consumption of intact oat kernels was associated with significant reductions in postprandial blood glucose (−45.5 mmol x min/L; 95% CI: −80.1, −10.9 mmol x min/L; P  = 0.010) and insulin (−4.5 nmol x min/L; 95% CI: −7.1, −1.8 nmol x min/L; P  = 0.001) responses; the consumption of thick oat flakes was associated with significant reductions in postprandial blood glucose (−30.6 mmol x min/L; 95% CI: −40.4, −20.9 mmol x min/L; P  < 0.001) and insulin (−3.9 nmol x min/L; 95% CI: −5.3, −2.5 nmol x min/L; P  < 0.001) responses; but, the consumption of thin/quick/instant oat flakes was not associated with any effects on the postprandial blood glucose and insulin responses. Conclusions: A disruption in the structural integrity of the oat kernel is likely associated with a loss in the glycemic benefits of oats.